Eggplant planting using fertigation technology in UMP campus - UMP, PNC (2019)
In a move to fully utilise unused area in campus, UMP Technology Sdn. Bhd. (UMPT) which is wholly-owned by UMP Holdings Sdn. Bhd. and tasked to promote commercialisation activities of UMP products, has successfully cultivated eggplant using the fertigation technology at the university’s Gambang campus.